Pengabaian Nafkah ‘Iddah: Perspektif Hukum Syarak dan Undang-Undang Keluarga Islam di Malaysia - Nurul Afifah Balqeis Roslee; Muhammad Aunurrochi Mas’ad; Abdul Manan Ismail; Nurin Insyirah Salleh; Siti Khairiyah Abdul Aziz; Muti’ah Muhammad; Wan Najibah Wan Mohd Din (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2026)
International Conference of Postgraduate Students and Academics in Syariah and Law 2025 (INPAC 2025) “Advancing Malaysia Madani through Global Shariah and Legal Research.” Organized by the Faculty of Syariah and Law, Universiti Sains Islam Malaysia (USIM)